A Logic Fluorescent Chemosensor Based on Eu3+ Functionalized Cd‐MOFs for Sensing Fe3+ and Cu2+ Synchronously. Issue 3 (3rd December 2022) - Li, Pengcheng; Chen, Xiaohuan; Guo, Cui; Zou, Huijing; Chen, Ziyi; Liu, Bingjie; Liang, Wenjie; Cai, Jianfeng; Xu, Hai
Abstract: One of the most critical and yet unsolved issues is the effective monitoring of multiple heavy metal ions in complex systems through their specific function in fluorescence detection. In this work, luminescence‐active cadmium base metal‐organic frameworks (Cd‐MOFs) based on the planar and rigid π‐conjugated structure ligand benzo‐(1, 2;3, 4;5, 6)‐tris (thiophene‐2'‐carboxylic acid) (H3 BTTC) was chosen. A series of sensing experiments demonstrated that the Cd‐MOFs exhibits selective and sensitive response for Fe 3+ and Eu 3+ through fluorescence "turn off" and "antenna effect" respectively. In addition, the encapsulation of Eu 3+ inside the Cd‐MOFs (Eu 3+ @Cd‐MOFs) led to an excellent probe with dual emission. To this end, a programmable fluorescence platform was developed to detect Fe 3+ and Cu 2+, in which the emission peaks of both the ligand and Eu 3+ are completely quenched by Fe 3+ . The ratiometric detection of Cu 2+ leads to a decrease in Eu 3+ emission, while the ligand emission remains stable. To demonstrate the strategy, the fluorescence (Output) of Cd‐MOFs, Eu 3+ @Cd‐MOFs, and the analytes (Eu 3+, Fe 3+, and Cu 2+, input) achieved elementary Boolean logic operations (OR, NOR, AND) and they constitute a logic fluorescent chemosensor to analyze Fe 3+ and Cu 2+ synchronously. Abstract : The Cd‐MOFs exhibits selective and sensitive responses for Fe 3+ and Eu 3+ through fluorescence "turn off" and "antenna effect" respectively. The encapsulation of Eu 3+ inside the Cd‐MOFs (Eu 3+ @Cd‐MOFs) led to an excellent probe with dual emission, which the Fe 3+ and Cu 2+ present different quenching manners. To this end, a programmable fluorescence platform was developed to detect Fe 3+ and Cu 2+ synchronously. Inspired by the above results, a Bool molecule logic gate based on their fluorescence changing was devised.